Environmental and Human Health Stress around the Hygiene and Sanitation (HYSACAM) Refuse Dump Sites in Yaoundé, Centre Region, Cameroon - Lucia, Nkengazong; Irma , Kame Ngasse Ginette; Lem , Mbafor Fidelia; Joisiane, Ojong Lucie; Bosco , Taya; Marie , Ngonde Chantal; Nyunaï , Nyemb (Current Innovations in Disease and Health Research Vol. 4, 2023)
Background: Increase urbanization in some developing countries contributes to increase household waste production. Inappropriate management of these wastes associated to environmental factors is crucial in the proliferation and dissemination of pathogens. The anarchic urbanism of Yaoundé has led to an increase in the rate of household wastes that constitute a favourable environment for the development of infecting agents, posing an important public health problem. Aim: This study was aimed to investigate the presence of infecting agents and impact on neighbourhood population health stress around the refuse dumpsites collection points in Yaounde. Study Design: During the prospective and cross-sectional study 60 environmental samples (soil and water) were collected from March to August 2019 from sixty refuse dump samples while 250 stool samples were collected from the neighbourhood populations aged 4 to 60 years from 12 quarters from November 2019 to February 2020. Methodology: Environmental samples were analysed using the Ritchie, flotation zinc sulphate and saturated salt centrifugation techniques. Stool samples were analyzed with the qualitative formalin ether and quantitative Kato-Katz technics. Risk factors related to contamination were evaluated through administered questionnaires to volunteer participants. Results: Environmental occurrence rate of pathogens resistant forms (51.7%) responsible for infectious diseases including: Geohelminthiasis (60.0%: A. lumbricoides; T. trichiura and hookworms; Schistosomiasis (20.0%: Schistosoma intercalatum) and zoonotic diseases (Fascioliasis (20.0%: :Fasciola hepatica). The Ritchie technique revealed statistically high number of infective agents (P= 0.003). 209 (82.9%) individuals were infested with at least one species of intestinal pathogens responsible for geo-helminthiasis (16.7%): Ascaris lumbricoides (12.3%), Trichirus trichiura (3.2%), hookworms (5.5%); Protozosis: Entamoeba histolytica (11.5%) and Entamoeba coli (13.5%), and intestinal candidiasis: Candida sp. (76.1%). Infection rate varied significantly by neighborhood (P= 0.02). Potential risk factors related to contamination included distance between residence and collection point (P= 0.004); the date of the last deworming (P= 0.003); hand washing with soap before meals (P = 0.001); frequency of abdominal pain (P= 0.001); promiscuity (P= 0.005); source of water supply (P= 0.002) and the distance between the water source and the collection point (P = 0.006). Conclusion: The presence of human-zoonotic diseases infective agents around the refuse dump sites collection points and health stress in neighborhood population indicate that the dumpsites are favorable milieu for pathogens proliferation and dissemination. This creates awareness for the authorities in charged to improve on the management of dumpsites and waste collection in Cameroon in order to overcome subsequent diseases outbreaks.